Community prevention in Lima: contributions of the Junta Vecinal - Huaytalla, Arturo (2019)
More than two decades have passed since the creation of the Junta Vecinal de Seguridad Ciudadana (Neighborhood Citizen Security Board) as an organization promoted and organized by the National Police of Peru. However, despite the time, and though it may seem strange, it is not presently clear how the Neighborhood Board contributes to citizen security. This article unravels the main contributions of the largest urban security organization in Peru, highlighting the different contexts.